Digital Discourse on "Politainment" Tiktok #Jogetgemoy From the Perspective of Digital Heterotopia - Wahyudi, Agus; Satrya Wibawa, Igak; Ariani Arimbi, Diah (The Journal of Society and Media, 2026)
This study explores the phenomenon of #JogetGemoy on TikTok as a form of politainment, where political campaigns are transformed into entertaining and emotionally engaging performances, particularly targeting Gen Z voters in Indonesia's 2024 presidential election. Utilizing Norman Fairclough’s Critical Discourse Analysis (CDA) combined with Roland Barthes’ semiotic framework, this research examines how texts, visuals, and hashtags in TikTok videos contribute to reshaping Prabowo Subianto's political image through affective and playful representations. The concept of digital heterotopia is employed to explain TikTok as an alternative public sphere in which contradictory social orders coexist, thereby normalizing a populist yet entertaining political discourse. The findings reveal that pleasure-driven visual and musical elements in #JogetGemoy content foster collective identity and reinforce positive perceptions of the candidate while obscuring policy narratives and critical debate. This politainment practice reflects a shift in political communication strategies, transforming politics from rational debate to a spectacle of pleasure and viral engagement. The study highlights how algorithmic culture, audience participation, and intertextual memes collaboratively produce an affective space of political discourse, which may have profound implications for the quality of democracy and civic engagement in Indonesia.